Study on fractional order grey reducing generation operator. Issue 1 (1st February 2016) - Meng, Wei; Li, Qian; Zeng, Bo
Abstract : Purpose: – The purpose of this paper is to derive the analytical expression of fractional order reducing generation operator (or inverse accumulating generating operation) and study its properties. Design/methodology/approach: – This disaggregation method includes three main steps. First, by utilizing Gamma function expanded for integer factorial, this paper expands one order reducing generation operator into integer order reducing generation operator and fractional order reducing generation operator, and gives the analytical expression of fractional order reducing generation operator. Then, studies the commutative law and exponential law of fractional order reducing generation operator. Lastly, gives several examples of fractional order reducing generation operator and verifies the commutative law and exponential law of fractional order reducing generation operator. Findings: – The authors pull the analytical expression of fractional order reducing generation operator and verify that fractional order reducing generation operator satisfies commutative law and exponential law. Practical implications: – Expanding the reducing generation operator would help develop grey prediction model with fractional order operators and widen the application fields of grey prediction models. Originality/value: – The analytical expression of fractional order reducing generation operator, properties of commutative law and exponential law for fractional order reducing generation operator are first studied.